Multi-Level Multi-Constraint Multi-Priority Fuzzy Sensor Routing (M3L-C-PFSR) - Agarkhed, Jayashree; Kadrolli, Vijayalaxmi; Patil, Siddaram (International journal of innovative technology and exploring engineering, 2019)
In the field of Wireless Sensor Network (WSN), real time applications, the interesting research emerged in the field of QoS routing. Networks must address resource constraints although providing an accurate guarantee of quality of service (PDR, throughput, energy, End-to-End delay).This document presents the routing protocol compatible with QoS, namely [M3L-C-PFSR] Multilevel, Multi constraint Multi Priority Fuzzy Sensor Routing Protocol which gives priority for important packets of important applications and also ensures the PDR, delay and throughput. Applying a scheme of multi level fuzzy based efficient buffer management to limit packet loss due to overflow. It supports lower throughput for packets which are lower in priority and higher throughput will be given for real-time prioritized packets which are assigned privileged higher priority, thus reducing end-to-end delay. The proposed work performance will be appraised [M3L-C-PFSR] in NS2. The results of the simulation depicts that the proposed protocol [M3L-C-PFSR] effectively minimizes the losses of critical packet, with different traffic conditions, ensuring the reliability and required delivery of data.